Cyclic behaviour of beam-to-column joints with cast steel connectors. (January 2016) - Tong, Lewei; Chen, Yingzhi; Chen, Yiyi; Fang, Cheng
Abstract: This paper presents a comprehensive study on steel beam-to-column joints equipped with weld-free cast steel connectors used as replaceable energy-dissipating components. The basic idea was to use the connectors as the main source of deformation and energy dissipation, and to realize rapid repair of the joints by simple replacement of theses connectors after earthquakes. The research commenced with tests on five full scale specimens, including one specimen with conventional welded T-stub connectors and four specimens with the innovative cast steel connectors. The specimens with cast steel connectors were shown to have good energy dissipation capacity with stable and plump hysteretic curves, and the equivalent viscous damping could achieve up to 37.5%. These joints were also shown to meet the classification criteria of semi-rigid joints in terms of stiffness, and the ductility, which was governed by fracture of energy dissipating elements, was found to be satisfactory. The presence of shear tab connection was found to increase the initial stiffness and ultimate strength of the joints, but the energy dissipation was not significantly improved. Importantly, the yielding regions and main source of energy dissipation were limited to the cast steel connectors, while the adjacent structural members remained in the elastic range, indicating minimal repair work in the aftermath of earthquakes. For a further understanding of the proposed joints, finite element models were established, and based on test and numerical observations, preliminary design recommendations, including those on cast steel connector detailing and normal component-based joint design strategies, were finally outlined. Highlights: Beam-to-column joints with new types of cast steel connectors were tested. The innovative joints have satisfactory energy dissipation capacity and ductility. Finite element modelling for the joints is developed. Preliminary joint design strategy for the joints is proposed.